A Lexico-Semantic Analysis of Selected Press Releases of The Indigenous People of Biafra (IPOB) - Emmanuel Jolaolu Adegbenro; Samson Adeyeye Dare; Chritianah Taiwo Obarotimi (Edulitics (Education, Literature, and Linguistics) Journal, 2025)
The Indigenous People of Biafra (IPOB), a new separatist movement in Eastern Nigeria, has been labelled a terrorist group by the Nigerian government against its stated goals. This study aims to investigate the language used in the IPOB’s press releases to identify the specific stylistic choices that contributed to its designation as a terrorist organisation. Four speeches from three prominent leaders of IPOB were purposively selected from the online spaces for the study; two from Mazi Uchenna Asiegbu and one each from Mazi Chika Edoziem and Mazi Nnamdi Kanu, respectively. Using Halliday’s theoretical framework of the Systemic Functional Grammar through a qualitative analysis, the selected speeches were first closely read; thereafter, the prominent lexico-sematic features that characterise the speeches were identified, categorised, and discussed. Findings revealed that the press releases were replete with the deployment of three lexico-semantic features, such as collocation, lexical relations, and figurative language, which were stylistically used to convey speakers’ intentions of grieving, protesting, self-defending, and calling for international aid. It further revealed that the manner of agitation, particularly brutality, informed their choice of negative words. The study concluded that the aggressive language patterns of the IPOB writers and their propaganda became the critical rhetorical techniques through which they were being labelled. This research will help to give insight into the specific lexical items chosen by the IPOB to construct identity, resistance, ideologies, emotions, and political positions.